Broadband Transmission and Statistical Performance Properties of Overhead High-Voltage Transmission Networks. (31st May 2012) - Lazaropoulos, Athanasios G.
Abstract : This paper considers broadband signal transmission and statistical performance properties of high-voltage/broadband over power lines (HV/BPL) channels associated with overhead power transmission. The overhead HV/BPL transmission channel is investigated with regard to its spectral behavior, its end-to-end signal attenuation, and its statistical performance metrics. It is found that the above features depend critically on the frequency, the overhead HV power grid type (150 kV, 275 kV, or 400 kV and single- or double-circuit), the coupling scheme applied, the physical properties of the cables used, the MTL configuration, and the type of branches existing along the end-to-end BPL signal propagation. The contribution of this paper is threefold. First, the significant broadband transmission potential of overhead HV lines is revealed. The results demonstrate that, regardless of overhead HV power grid type, the overhead HV grid is a potentially excellent communications medium, offering low-loss characteristics, flat-fading features, and low multipath dispersion over a 25 km repeater span well beyond 100 MHz. Second, regarding the statistical properties of various overhead HV/BPL transmission channels, two fundamental correlations of several wireline systems, for example, coaxial cables and xDSL, are also validated in the case of overhead HV/BPL transmission channels, namely, (i) end-to-end channel attenuation in relation with root-mean-square delay spread (RMS-DS) and (ii) coherence bandwidth (CB) in relation with RMS-DS. Third, fitting the numerical results and other field trial measurements, two regression distributions suitable for each fundamental correlation are proposed.